2014
DOI: 10.3389/fpsyg.2013.00973
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenology of meditation-induced light experiences: traditional buddhist and neurobiological perspectives

Abstract: The scientific study of Buddhist meditation has proceeded without much attention to Buddhist literature that details the range of psychological and physiological changes thought to occur during meditation. This paper presents reports of various meditation-induced light experiences derived from American Buddhist practitioners. The reports of light experiences are classified into two main types: discrete lightforms and patterned or diffuse lights. Similar phenomena are well documented in traditional Buddhist tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 101 publications
4
49
0
1
Order By: Relevance
“…AF mastered his ability to give light after decades of silent vigils in French cathedrals and thus his meditation method is clearly idiosyncratic, although his description suggests more like an objectless meditation rather than an object driven state. Although the precise nature of this very large increase of gamma oscillations is difficult to decipher, we suggest that this could be related to with intense spontaneous visual imagery as experienced during "encounters with light" phenomenon (Lo, Huang et al, 2003;Lindahl, Kaplan et al, 2014). Interestingly, a recent paper (Braboszcz, Cahn et al, 2017) has studied Isha Shoonya meditation, which is based on a related concept "nothingness/ doing nothing", and found high gamma synchronization in both parietooccipital and frontal regions during meditation; the results are interpreted in terms of higher top-down control mediated by frontal oscillations (Ossandon, Vidal et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…AF mastered his ability to give light after decades of silent vigils in French cathedrals and thus his meditation method is clearly idiosyncratic, although his description suggests more like an objectless meditation rather than an object driven state. Although the precise nature of this very large increase of gamma oscillations is difficult to decipher, we suggest that this could be related to with intense spontaneous visual imagery as experienced during "encounters with light" phenomenon (Lo, Huang et al, 2003;Lindahl, Kaplan et al, 2014). Interestingly, a recent paper (Braboszcz, Cahn et al, 2017) has studied Isha Shoonya meditation, which is based on a related concept "nothingness/ doing nothing", and found high gamma synchronization in both parietooccipital and frontal regions during meditation; the results are interpreted in terms of higher top-down control mediated by frontal oscillations (Ossandon, Vidal et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…However, to our knowledge, no study so far has connected the documented increase in occipital gamma during meditation with spontaneous visual imagery. Interestingly, the process of "seeing things" during meditation is a commonly reported phenomenon -"encounters with light" -amongst meditators (Lo, Huang et al, 2003, Lindahl, Kaplan et al, 2014. For example, Lindahl, Kaplan et al (2014) wrote "Two practitioners also reported a proprioceptive dimension to their meditationinduced light experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of this study was inspired by the “Varieties of Contemplative Experience” project [45,46]. Inclusion criteria for participants were: being at least 18 years of age, having Anthroposophic meditation as a main element of their meditation practice, having a regular meditation practice of at least one year, and having experienced at least one significant or unexpected effect of meditation, whether positive or negative.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Changes in the perceptual domain range from benign and even expected experiences such as hypersensitivity to light, sound, or body sensations, to more unusual and unexpected experiences such as distortions in space and time, derealization, and visions or visual hallucinations. Reports of visual lights are given varied appraisals across Buddhist traditions ranging from an unimportant side-effect of practice to a sign of progress in concentration that should become a new meditation object (Lindahl et al, 2014). A qualitative study of advanced Burmese meditators documented increased perceptual sensitivity and clarity, which were framed in terms of a valued insight into impermanence (Full et al, 2013).…”
Section: Perceptual Changesmentioning
confidence: 99%